INTERAKSI DAN HUBUNGAN PARASOSIAL DI MEDIA SOSIAL (STUDI DESKRIPTIF PADA PENGGEMAR STRAY KIDS DI TWITTER) - Anindya Nusakinanti, (2022)
The development of information and communication technology, mainly on social media, provides an opportunity to spread the K-Pop industry, including to Indonesia. K-Pop groups especially the 4th generation optimizing the use of social media to post about information and contents to interact with their fans. The existence of constant social media contents from idols create a sense of pseudo-closeness that only felt by their fans. This pseudo-closeness phenomenon started with parasocial interaction that formed a parasocial relationship. By using descriptive qualitative research methodology and constructivism paradigm, this study tries to analyze the process of social interaction on Twitter by Stay (Stray Kids fans) and the social relationship that forms between Stay and Stray Kids. Data obtained through interviews, observations, and documentation with the criteria of informants which are Stray Kids fan at least for 1 year and a user of Twitter, and the data analyzed using the PSI-Process Scale. The results of this study show that all informants were active in conducting parasocial interactions with Stray Kids on Twitter by going through the cognitive responses, affective responses, and behavioral responses. It shows that the informants formed parasocial relationship by constructing pseudo-relationship and experiencing its effects